Effect of Perforation Size on Sound Absorption Characteristics of Membrane Absorber - Hamdan, Nur Izzah; Zainulabidin, Muhd. Hafeez; Kasron, Md Zainorin; Mohd Kassim, Angzzas Sari; Ismail, Al Emran (International Journal of Integrated Engineering, 2018)
This paper describes the analysis on the sound absorption characteristics of perforated membrane absorber. This study aimed to investigate the effect of perforation sizes and percentage of perforation areas on the membrane sound absorption characteristic. The effects of physical and material properties of the membranes such as thickness, Young’s modulus and density were also investigated. The characteristics of the perforated membrane absorber were measured experimentally in terms of Sound Absorption Coefficient, α and Noise Reduction Coefficient, NRC by utilizing impedance tube method in compliance with ISO 10534-2 standard. The results showed that the peak value of absorption coefficient is determined by the density and thickness of the membranes. The perforation sizes also have a significant effect on the sound absorption coefficient and frequency range width. Optimal perforation size enhances the sound absorption performance of the membrane. Overall, the perforated membranes give better sound absorption coefficient and wider frequency range compared to the unperforated membranes.